2014
DOI: 10.1134/s0012500814080023
|View full text |Cite
|
Sign up to set email alerts
|

New nanobiocomposites of ammonium magnesium phosphate and carrageenan as efficient prebiotics

Abstract: It is known that normal functioning of a human or animal body requires a balanced qualitative and quan titative composition of intestinal microbiocenosis [1,2]. The intestinal microflora forms the systemic and tissue immunity, and participates in the fat and pigment metabolism, digestive enzyme production, and endogenous synthesis of vitamins and substances hav ing bactericidal action on pathogenic organisms [3,4]. A considerable stimulating effect on the generation, growth, and functional activity of the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…[22][23][24] For this purpose,  polysaccharides are usually used in the native form; 22-24 however, they can also be used as components of even more effective multi element prebiotic mineral-poly saccharide composite nanoconstructs. 25 In the past years, prebiotics, particularly in different combinations with probiotics (beneficial microorganisms), are consid ered as a natural and highly efficient alternative to an tibiotics. 26 Arabinogalactan extracted from Siberian larch 27,28 is a promising prebiotic  heteropolysaccharide of plant cell walls, 29 but industrially obtained species of arabinogalac tan contain phenolic impurities.…”
mentioning
confidence: 99%
“…[22][23][24] For this purpose,  polysaccharides are usually used in the native form; 22-24 however, they can also be used as components of even more effective multi element prebiotic mineral-poly saccharide composite nanoconstructs. 25 In the past years, prebiotics, particularly in different combinations with probiotics (beneficial microorganisms), are consid ered as a natural and highly efficient alternative to an tibiotics. 26 Arabinogalactan extracted from Siberian larch 27,28 is a promising prebiotic  heteropolysaccharide of plant cell walls, 29 but industrially obtained species of arabinogalac tan contain phenolic impurities.…”
mentioning
confidence: 99%
“…Carrageenan and galactomannan and, to a greater extent, their nanocomposites, stimulate growth and biological activity of lactic acid bacteria, of probiotic strains of Bacillus amyloliquefaciens subsp. plantarum UCМ В-5139 and UCM В-5140, and, in addition, exhibit immunomodulatory properties [6,7]. Previously, we showed that the Bacillus strains UCM B-5139 and UCM B-5140 themselves synthesize a number of biologically active substances including polysaccharides, which can be key players that determine their probiotic activity.…”
mentioning
confidence: 99%
“…These bacteria are the components of the probiotic "Endosporin" [5]. Bacteria strains were cultivated on synthetic medium [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Arabinogalactan was chosen as a scaffold for the composite preparation due to the polysaccharide water solubility and biocompatibility allowing its application in nanocomposite biomedical systems [9][10][11][12][13][14][15].…”
mentioning
confidence: 99%